2016
DOI: 10.1074/jbc.m116.752063
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomal Degradation of the EWS-FLI1 Fusion Protein Is Regulated by a Single Lysine Residue

Abstract: Edited by George DeMartinoEHere, we identify the EWS-FLI1 protein as a substrate of the ubiquitin-proteasome system with a characteristic polyubiquitination pattern. Using a global protein stability approach, we determined the half-life of EWS-FLI1 to lie between 2 and 4 h, whereas full-length EWSR1 and FLI1 were more stable. By mass spectrometry, we identified two ubiquitin acceptor lysine residues of which only mutation of Lys-380 in the ETS domain of the FLI1 part abolished EWS-FLI1 ubiquitination and stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 61 publications
(56 reference statements)
0
29
0
Order By: Relevance
“…AZD8055 inhibits the phosphorylation of mTORC1 substrates p70S6K and 4E-BP1 as well as phosphorylation of the mTORC2 substrate AKT and downstream proteins [ 38 ]. Moreover, 3-methyladenine (3-MA) inhibits class III PI3K and is widely used as an autophagy inhibitor in various studies [ 39 , 40 ]. Interestingly, our in vivo data showed that systemic administration of a mTOR inhibitor (AZD8055) or a mTOR-dependent autophagy stimulator (rapamycin) to LPS-treated mice significantly ameliorated gut inflammation and oxidant stress as shown by decreased body weight loss and histological damage, where the inhibition of autophagy by 3-MA in LPS-treated mice remarkably aggravated oxidative injury and histological damage.…”
Section: Discussionmentioning
confidence: 99%
“…AZD8055 inhibits the phosphorylation of mTORC1 substrates p70S6K and 4E-BP1 as well as phosphorylation of the mTORC2 substrate AKT and downstream proteins [ 38 ]. Moreover, 3-methyladenine (3-MA) inhibits class III PI3K and is widely used as an autophagy inhibitor in various studies [ 39 , 40 ]. Interestingly, our in vivo data showed that systemic administration of a mTOR inhibitor (AZD8055) or a mTOR-dependent autophagy stimulator (rapamycin) to LPS-treated mice significantly ameliorated gut inflammation and oxidant stress as shown by decreased body weight loss and histological damage, where the inhibition of autophagy by 3-MA in LPS-treated mice remarkably aggravated oxidative injury and histological damage.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour cells characteristically express fusion proteins with an N-terminal region derived from EWS, a poorly characterised RNA-binding protein, and C-terminal region from FLI-1, or less frequently ERG, including the ETS domain. EWS-FLI-1 fusions are short-lived proteins that become ubiquitinated in the ETS domain and turned over by the UPS, although the E3 ubiquitin ligase responsible remains to be identified [ 60 ]. Of note, the same lysine (K334: = K388 in ETS-1) was also ubiquitinated on FLI-1.…”
Section: Erg Fusion Proteins and The Evasion Of Ubiquitin-mediated Proteolysis In Prostate Cancermentioning
confidence: 99%
“…The effects of EWSR1 on genes also targeted by the fusion protein are remarkably similar. Our result that hundreds of genes can be affected by both EWS-FLI1 and EWSR1 may be a lower estimate, because EWSR1 concentrations in the cell are quite high (~8 µM) and proteomics studies have indicated levels of endogenous EWS-FLI1 to be much lower (Elzi et al 2014;Hein et al 2015;Gierisch et al 2016). Consequently, siRNA knockdown may more effectively abolish the activity of EWS-FLI1, resulting in effects that were seen for more genes and changes to transcript levels that were generally greater than those found with the EWSR1 knockdown.…”
Section: Several Mechanisms May Contribute To the Ability Of Ews-fli1mentioning
confidence: 70%